Religion and Academic Achievement: A Research Review Spanning Secondary School and Higher Education - Horwitz, Ilana M. (Review of religious research, 2021)
Profound socio-economic disparities that exist among American religious groups are largely driven by the quantity and quality of education they receive. Furthermore, given the U.S. schooling system is rooted in Protestant ideals, it is possible that students with Protestant commitments have an academic advantage. This article synthesizes literature on how adolescents’ religious commitment and background are associated with their short- and long-term academic outcomes. A literature search identified 42 relevant studies published in 1990-present. These studies were reviewed to identify: (1) the mechanisms through which religion affects educational outcomes—moral, social, and cultural; (2) the main operationalized measures of religion—religious tradition and individual religiosity; and (3) the most frequent academic outcomes studied—secondary school grades, truancy, test scores, educational aspirations, and educational attainment. Of the 42 studies, 95% were based exclusively on quantitative survey data, 95% examined only religiosity or religious tradition, and 66% focused on educational attainment. There were three major findings. First, research has advanced from correlational studies to methodologically rigorous designs suggesting religion can play a causal role in academic success. Second, research reveals a religiosity-religious tradition paradox: Adolescents with stronger religiosity earn better grades, are less truant in secondary school, and complete more years of higher education. A large proportion of highly religious adolescents are likely to be conservative Protestants, but the research on religious tradition suggests that conservative Protestants are among the least educated religious groups. Third, it is unclear if religious adolescents only fare better on academic outcomes that reward their personality, such as grades, or whether they also perform better on more objective measures, such as standardized tests. This systematic review reveals a paradoxical “effect” of academic achievement and religiosity versus-religious tradition. The overall results indicate the need to: (a) identify the interaction between religious tradition and religiosity, (b) distinguish between subjective versus objective academic outcomes; (c) examine heterogeneity among non-religious adolescents; (d) study the interplay between institutional schooling and institutional religion; (e) investigate the religion/cultural match between teachers and students; (f) pursue qualitative research to better understand mechanisms; and (g) expand research about non-Christians.